Antara Cerita dan Sejarah: Meriam Cetbang Majapahit - Averoes, Muhammad (Jurnal Sejarah, 2020)
This research was intended to trace the origin and the form of the Majapahit cetbang cannon. In many medias, cetbang is said to be a Majapahit weapon that was developed from Mongol gunpowder weapons obtained during the Mongol-Chinese attack on Java. The cetbang was described as a breech-loading swivel gun, but the Mongol-Chinese gunpowder weapon was very different from the breech-loading swivel gun. This paper investigated the cetbang cannon based on philological studies, its references in old Javanese language, and similar cannon from other parts of the world.